A new deep-bodied Late Permian actinopterygian fish from the Beaufort Group, South Africa - Bender, Patrick (BERNARD PRICE INSTITUTE FOR PALAEONTOLOGICAL RESEARCH, 2005)
Anew genus of actinopterygian (ray-finned) fish, Blourugia seeleyi is described from Late Permian (Tatarian) fluvio-lacustrine, siltstone dominated deposits within the lower Beaufort Group of South Africa. It was originally provisionally assigned to the globally known genus Atherstonia by Woodward (1893), but indications are that the genus is distinct from Atherstonia on the basis of its deep-bodied form and the associated skull characters; thus Blourugia seeleyi is placed in Gardiner&Schaeffer’s (1989) Platysomus Group. The new genus is characterized by a uniquely shaped prominent high triangular posterior blade of the maxilla, dermosphenotic triangular shaped, pointed marginal teeth, 8–10 branchiostegal rays, flank scales that exhibit a well-developed dermal ornamentation consisting of numerous transverse ganoine ridges, and the presence of a dermopterotic that contacts the nasal. Blourugia appears to be a primitive deep-bodied form, basal to lower actinopterygian deep-bodied forms such as Adroichthys, Amphicentrum, Cheirodopsis, Paramesolepis and Platysomus. As a member of Gardiner & Schaeffer’s Platysomus Group, it is therefore derived relative to stem-actinopterans such as Howqualepis, Mimia and Moythomasia, and also derived relative to earlier southern African Palaeozoic actinopterygians such as Atherstonia scutata, Mentzichthys jubbi, Namaichthys schroederi and the newly/recently described lower Beaufort Group taxa Bethesdaichthys kitchingi and Kompasia delaharpei, but basal to stem-neopterygians such as Australosomus and Saurichthys.